A solution-processable copper(ii) phthalocyanine derivative as a dopant-free hole-transporting material for efficient and stable carbon counter electrode-based perovskite solar cells. Issue 34 (18th August 2017) - Jiang, Xiaoqing; Yu, Ze; Li, Hai-Bei; Zhao, Yawei; Qu, Jishuang; Lai, Jianbo; Ma, Wanying; Wang, Dongping; Yang, Xichuan; Sun, Licheng
Abstract : A solution-processable copper(ii ) phthalocyanine derivativeCuPc-TIPS has been explored as a dopant-free hole-transporting material in carbon counter electrode-based perovskite solar cells. Abstract : A solution-processable copper(ii ) phthalocyanine derivative coded asCuPc-TIPS has been synthesized and adopted as a hole-transporting material (HTM) in perovskite solar cells (PSCs), in combination with a mixed-ion perovskite absorber and a low-cost carbon cathode. Optimised PSC devices based on pristineCuPc-TIPS without any additives or dopants show a decent power conversion efficiency of 14.0% (measured at 100 mW cm −2 illumination, AM 1.5G), together with a good long-term stability under ambient conditions. The present finding highlights the potential of solution-processed copper phthalocyanine derivative-based HTMs for the development of efficient and stable PSCs in the future.